Radical "Boyhood" Futures for the Twenty-First Century, or, Pinocchio (Finally) Gets His Phallus. Issue 3 (3rd July 2019) - Hammer, K. Allison
ABSTRACT: This article considers radical "boyhood" futures for the twenty-first century and the ways transmasculine subjects are creating exuberant, phallic subjectivities through working the gap between body and psyche. In Female Masculinity, Jack Halberstam asked, "What happens when boy rebellion is located not in the testosterone-induced pout of the hooligan but in the sneer of the tomboy?" Recent transgender movements compel a revision of this question, for what if boy rebellion is located precisely in this "testosterone-induced pout" but in the body of a child or adult assigned female at birth? Availability and advances in medical technologies allow boyhood to occur at any stage of life, in effect queering the life cycle, while new cultural production and community support systems offer unprecedented opportunities for change. Some of these developments suggest how Pinocchio and other childhood stories become important touchstones used by transmasculine subjects to construct their own boyhoods. The 2016 documentary Real Boy tells the story of a young musician who transitions from female to male despite his family's rejection. "Camp Lost Boys" offers transmasculine folks the experience of summer camp, a place to reflect on what it means to be masculine. Responding to the problem of White transnormativity, the 2012 documentary The Aggressives by Daniel Peddle brings to a larger audience the struggles that trans* subjects of color assigned female at birth experience endure due to economic precarity, violence, and the prison industrial complex (PIC). "Brown Boi Project" helps trans* folks to ask what it can mean to be a man or a boy in communities of color. Testifying to their power, nonnormative boyhoods augment existing anxiety and resentment among White, cisgendered men, helping to perpetuate the self-created "state of emergency" over POCs (people of color), women, and LGBT (lesbian, gay, bisexual, transgender) persons "infiltrating" (in their minds), the heteronormative, cisgendered "mainstream." The violent reactions of White supremacist men's groups suggest how the transmasculine tampers with the sanctity of boyhood, disturbing what Homi K. Bhabha calls the "manifest destiny" of masculinity.